2020
DOI: 10.1002/slct.202000043
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pyruvate Kinase (PK) Inhibitors: New Target to Overcome Bacterial Resistance

Abstract: In the present investigation, some novel nitro Mannich bases derived from Michael type addition of activated nitro olefin, β‐nitrostyrene with various amines either primary or secondary including some amino sugars were designed and synthesized. The produced Mannich bases have been full characterized through different spectroscopic techniques. Antimicrobial evaluation has been performed against the Gram positive S. aureus and methicillin‐resistant S. aurues (MRSA) infections. 5 of the synthesized compounds repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Compound 13 e demonstrated PK independent bacteriostatic and PK dependent bactericidal properties. [50] Other chemotypes such as 1,3-di(1H-indol-3-yl)-1,2,3,4tetrahydrocycloalka[b]indoles, [52] indole carboxamides, [51] phenyl indoles, [51] 2-heteryl indoles, [51] (4-(1H-indol-3-yl)thiazol-2-yl)(1Hindol-3-yl)methanones, [53] N-benzylbenzo[d]thiazol-2-amine, [51] and nitro mannich bases [55] demonstrated good to moderate inhibition against SAPK and whole S. aureus bacterial cells. ChemistrySelect…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 13 e demonstrated PK independent bacteriostatic and PK dependent bactericidal properties. [50] Other chemotypes such as 1,3-di(1H-indol-3-yl)-1,2,3,4tetrahydrocycloalka[b]indoles, [52] indole carboxamides, [51] phenyl indoles, [51] 2-heteryl indoles, [51] (4-(1H-indol-3-yl)thiazol-2-yl)(1Hindol-3-yl)methanones, [53] N-benzylbenzo[d]thiazol-2-amine, [51] and nitro mannich bases [55] demonstrated good to moderate inhibition against SAPK and whole S. aureus bacterial cells. ChemistrySelect…”
Section: Discussionmentioning
confidence: 99%
“…Sayed et al [55] reported synthesis of new mannich bases from βnitrostyrene through Michael type addition with different type of amines/amino sugars (Figure 16). Among them, nitro mannich bases 22 a and 22 b displayed moderate inhibition against bacterial PK with IC 50 662.98 ng/mL and 418.72 ng/mL, respectively.…”
Section: Nitro Mannich Basesmentioning
confidence: 99%
See 1 more Smart Citation
“…e synthesized compounds (16)(17)(18)(19)(20)(21)(22)(23)(24) were subjected to a molecular docking analysis to determine their binding affinity towards pyruvate kinase in a complex containing the natural bisindole alkaloid, and the results were compared to amoxicillin (SI Appendix D Figure S5(c), 1-10, and Table S9) [59,60]. It was found that the synthesized compounds have minimum binding energy in the range of is suggests that these compounds are effective antibacterial agents against S. aureus.…”
Section: Molecular Docking Studies Of Synthesized Compoundsmentioning
confidence: 99%
“…At the same time, the ligand is hydrogenated, charged, and protonated. The active site of pyruvate kinase was prepared according to the study of El Sayed et al (2020). The platform is used to identify the binding site of phosphofructokinase.…”
Section: Molecular Dockingmentioning
confidence: 99%